Etno-Arsitektur Umpak-Umpak Batu Tinggalan Budaya Megalitik Masa Protohistori di Lembah Behoa, Kabupaten Poso, Provinsi Sulawesi Tengah - Kriswandhono, Albertus; Yuniawati Umar, Dwi Yani (Badan Riset dan Inovasi Nasional, 2022)
Several structural stones were discovered during research in 1995 – 2004 in Behoa Valley that, if a line is drawn, would form a rectangular polygon with two types of stone, large and small. In 2013, researchers conducted an ethno-architectural study at three megalithic cultural heritage sites in Hanggira Village. The aim is to find out the function of these structured stones. From the results of the ethno-architecture analysis, these structured stones are umpak foundations from dwellings or residential places (Tambi) or places to store special goods or agricultural products (Buho). There is no absolute chronology in the context of the structured stones in the form of umpak foundations. However, from the age of the site, it is expected that these stone umpak foundations had been used since the beginning of the AD century (early metal period) to the protohistoric period.